2003
DOI: 10.1007/s00011-003-1173-9
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose acetate beads induce release of interleukin-1 receptor antagonist, but not tumour necrosis factor-α or interleukin-1β in human peripheral blood

Abstract: These results indicate that CA beads selectively induce IL-1ra release from leucocytes which should contribute to the anti-inflammatory effect of granulocyte and monocyte adsorptive apheresis with CA beads as apheresis carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 17 publications
0
30
1
Order By: Relevance
“…We have previously demonstrated in in vitro studies that IL-1ra, which binds to IL-1RI and inhibits IL-1 signaling in leukocytes [28,29], is selectively released by GMs that adhere to the Adacolumn carriers [27,30]. Further, under identical conditions, pro-inflammatory cytokines like TNF-α and IL-1β were not measurable [30]. Similarly, in this study, IL-1α and IL-1β in plasma were not detectable during GMA in these patients.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We have previously demonstrated in in vitro studies that IL-1ra, which binds to IL-1RI and inhibits IL-1 signaling in leukocytes [28,29], is selectively released by GMs that adhere to the Adacolumn carriers [27,30]. Further, under identical conditions, pro-inflammatory cytokines like TNF-α and IL-1β were not measurable [30]. Similarly, in this study, IL-1α and IL-1β in plasma were not detectable during GMA in these patients.…”
Section: Discussioncontrasting
confidence: 69%
“…The rise in IL-1ra is attributable to interactions between granulocytes/monocytes and the column leukocytapheresis carriers and is adhesion dependent [27]. We have previously demonstrated in in vitro studies that IL-1ra, which binds to IL-1RI and inhibits IL-1 signaling in leukocytes [28,29], is selectively released by GMs that adhere to the Adacolumn carriers [27,30]. Further, under identical conditions, pro-inflammatory cytokines like TNF-α and IL-1β were not measurable [30].…”
Section: Discussionmentioning
confidence: 96%
“…Autologous serum was also prepared by centrifugation at 800 ¥ g for 5 min at 4°C after coagulation of blood, which was collected without an anticoagulant. The CA beads in saline were autoclaved and washed with saline as described previously [11,18]. The beads were incubated with or without plasma (in RPMI 1640) for 60 min at 37°C with gentle rotation at 1 rpm.…”
Section: Treatment Of Ca Beads With Plasma or Serummentioning
confidence: 99%
“…Our recent investigations have demonstrated that CA beads selectively induce release of anti-inflammatory cytokine IL-1ra, but not pro-inflammatory cytokines like tumour necrosis factor-a (TNF-a) or IL-1b [11]. The source of IL-1ra was considered to be GMs both of which extensively adsorb to CA beads [11]. Similarly, hepatocyte growth factor (HGF), which is an important contributor to tissue repair [12][13][14] is produced by activated GMs [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…– An increased production of anti-inflammatory IL-1 receptor antagonist (IL1-ra) [19, 20] and hepatocyte growth factor [21] were seen.…”
Section: The Adacolumn Leukocytapheresis System: Granulocytes-monocytmentioning
confidence: 99%